Effect of Averrhoa bilimbi Fruit Filtrate and Shrimp Paste Mixture on Performance, Gut Microbes and Blood Profile of Broilers - Indri Mareta; Gilbert Nathaniel; Turrini Yudiarti; Endang Widiastuti; Hanny Indrat Wahyuni; Sugiharto Sugiharto (Indonesian Center for Animal Research and Development (ICARD), 2020)
This study was aimed to evaluate effect of a mixture of Averrhoa bilimbi fruit filtrate and shrimp paste (Mysis sp.) on the growth performance, blood profile, selected intestinal bacterial number and pH value of broiler digestive tract. The mixture of A. bilimbi fruit filtrate and shrimp paste were incubated for 4 days and were then used in the experiment. For in vivo experiment, 40 day-old Lohmann broiler chicks were distributed randomly to two treatment groups, i.e., control (T1) and chickens given the mixture of 10% A. bilimbi fruit filtrate and shrimp paste in drinking water (T2). Body weight and feed intake were recorded weekly. At day 42, 2 birds from each pen (8 chicks per treatment group) were taken for blood and digesta collection. Internal organ weight and carcass traits were determined thereafter. Feed conversion ratio (FCR) was lower (P<0.05) on treatment group than control. Hemoglobin and mean corpuscular volume (MCV) of treatment group were higher (P<0.05) than that of control. Total cholesterol was higher (P<0.05) in treatment group than that in control. Total cecum coliform was lower (P<0.05) in treatment group than that in control. The pH values of the small intestinal segments (jejunum, ileum, cecum) was lower (P<0.05) in treatment group than that in control group. In conclusion, administration of the blends of A. bilimbi fruit filtrate and shrimp paste into drinking water improved FCR, increased hemoglobin and MCV values, decreased gut pH and cecal coliform of broiler chickens.